Kewenangan Pelelangan Kayu Hasil Illegal Loging - Zulham Adamy; Eko Nuriyatman (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
The existence of exploitation of forest resources that are dangerous for the survival of the forest is illegal logging activities carried out without going through a selection or selective logging process and permission from the government. So related to this, this scientific article discusses the